Feasibility of CAIPIRINHA-Dixon-TWIST-VIBE for dynamic contrast-enhanced MRI of the prostate. Issue 11 (November 2015) - Othman, Ahmed E.; Martirosian, Petros; Schraml, Christina; Taron, Jana; Weiss, Jakob; Bier, Georg; Schwentner, Christian; Nickel, Dominik; Bamberg, Fabian; Kramer, Ulrich; Nikolaou, Konstantin; Notohamiprodjo, Mike
Abstract: Purpose: To evaluate the feasibility of a CAIPIRINHA-Dixon-TWIST (CDT)-VIBE sequence for improving image quality and temporal resolution in dynamic contrast-enhanced MRI (DCE-MRI) of the prostate. Material and methods: 44 male patients (age 63.9 ± 8.9 years) with clinically suspected prostate cancer underwent DCE-MRI at a 3T MRI scanner (Magnetom Skyra, Siemens Healthcare, Erlangen, Germany) using a CDT-VIBE sequence (spatial resolution = 3 × 1.2 × 1.2 mm 3, temporal resolution = 5 s, total scan duration = 4:10 min) with body-weight-adapted administration of contrast agent (Gadobutrol, Bayer Healthcare, Berlin, Germany). To investigate effects on image quality, the same sequence was acquired three times per patient during the late phase: 1. with the same protocol as in the arterial phase (VS5), 2. without view-sharing (no view-sharing, NVS) using a 2-fold CAIPIRINHA acceleration R = 2 (temporal resolution = 15 s, NVS15) and 3. NVS using a 6-fold CAIPIRINHA acceleration R = 6 (temporal resolution = 5 s, NVS5). SNR and CNR were evaluated with the subtraction method. Image quality of the three sequences (VS5, NVS15, NVS5) was subjectively assessed by 2 blinded radiologists using a 5-point Likert scale (5 being excellent). Perfusion profiles of visually normal prostate and of malignant lesions as characterized by Wash-In, Wash-Out, time-to-peak (TTP) and initial area under the curve (iAUC) from the original datasets (temporal resolution = 5 s) and from datasets with a downsampled temporal resolution (15 s) were compared. Results: In 20 of 44 included patients, potentially malignant lesions were identified in which 16 had histologically confirmed prostate cancer. SNR was highest for VS5 and NVS15, and lowest for NVS5 ( p < .001). Concordantly, subjective image quality was comparable for VS5 and NVS15 (sum score 23.20 ± 1.03 vs 23.53 ± 1.34) and significantly lower for NVS5 (sum score 9.83 ± 2.32; p < .001). Perfusion parameters of macroscopically normal prostate tissue and suspect lesions differed significantly between original datasets and datasets with simulated lower temporal resolution, with the latter showing higher Wash-In ( p = .002), lower Wash-Out ( p = .003), higher Time-to-Peak ( p < .001) and lower iAUC ( p < .001). Conclusion: CDT-VIBE can be readily exploited for DCE-MRI of the prostate preserving the diagnostic image quality while providing high temporal resolution for quantitative diagnostic assessment of enhancement curves in malignant lesions.